Expanding the concept of Ba: managing enabling contexts in knowledge organizations (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
This paper investigates and analyses the concept of ba – or enabling context - in the fields of information science, management/business and information systems literature in order to understand its conceptual evolution, discussions, applications and expansion since its introduction in 1998 by Nonaka et al. (Nonaka and Konno, 1998; Nonaka et al., 2000; Nonaka and Toyama, 2002; Nonaka et al., 2006). The qualitative methodology is bibliographic and comprises – among others - the methods of citation analysis and content analysis. A resulting selection of 135 papers, 4 dissertations/theses and 4 books constituted the research’s final database. Data analysis consisted of three flows of activities: data reduction, data displays (conceptual maps) and conclusion drawing/verification. The results point out to the identification of four major groups of enabling conditions – social/behavioral, cognitive/epistemic, informational and business/managerial - which can be singly or freely combined into different knowledge processes – creation, sharing/transfer and use – occurring in different levels of interactions – individual, group, organizational, inter-organizational. The conclusions suggest that the concept of ba and its underlying concepts are indeed sine qua non conditions for organizational knowledge creation and innovation processes, though ba is still both theoretically and empirically under-explored. Concerning the management of enabling contexts in knowledge organizations, the study revealed that the main arising challenges rely on the implementation and development of the issues comprised on the four groups of enabling conditions identified, most especially social/behavioral and business/managerial.Keywords: The concept of Ba. Ba. Enabling context. Enabling conditions. Enabling knowledge creation. Knowledge management. Nonaka.Link para o texto completo (PDF)http://portaldeperiodicos.eci.ufmg.br/index.php/pci/article/view/1334/917